Financial Sector Reforms in Nigeria: a chronological overview - Umejiaku, Dr. Rose Ifeoma . (IJRDO - Journal of Applied Management Science, 2017)
Nigeria banking system over the years has undergone various phases that tend to have erodedconfidence on the side of the customers and investors due to the bank failure recorded in the past.These instabilities and bank failure in the Nigeria financial institution had limited credit expansionmeant for enhanced investment purposes and economic growth. The paper thus examined bankingsector in Nigeria, and highlighted various banking reforms carried out in the past since 1986. Ittracked the growth of the Nigeria banking sector in response to the reforms implemented over thepast three decades. It was discovered that Nigeria has enjoyed a substantial bank-based financialsector development over the years, and its institutional framework has also grown stronger. Theseframeworks were adopted to break the oligopolistic structure in the industry, to promote competition, creativity, increase capital base and efficiency in banking service delivery. However, theentire banking reform objectives have not been entirely achieved as few banks still controls largerpercent of deposit market and existence of high rates of non-performing loans within the bankingsystem remains a challenging task.